Carbon stock of the herbaceous layer under diferente plant cover in fragments of Caatinga - Ribeiro Filho, Jacques; Andrade, Eunice; Palácio, Helba; Moura, Matheus; Santos, Daniel (Revista Ciência Agronômica, 2021)
Climate change and the extensive areas of dry tropical forests (DTF) used in the production of pasture determine the need to investigate alternative managements that would make it possible to increase carbon stock. As such, the aim of this research was to estimate the carbon stock in the herbaceous layer of two fragments of seasonally dry tropical forest: i) a fragment of dry tropical forest under 40 years of regeneration and ii) forest submitted to the thinning of trees with a diameter